Analisis Implementasi Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja - Alam, Kodrat; Wira Perdana, Fadjrin; Irwan, Irwan; Lumban Tungkup, Doharman; Miran, Miran (Jurnal Indonesia Sosial Sains, 2022)
The stipulation of the Omnibus Law on the Job Creation Act as a regulation that regulates various sectors aims to improve the investment climate and willingness to establish a business in Indonesia in order to create wider job opportunities so that it can absorb more of the workforce. But in fact, the enactment of the Job Creation Law has actually caused a lot of turmoil and demonstrations in various regions in Indonesia because there are articles that are considered contradictory and can degrade rights and welfare, ignore environmental sustainability and the sustainability of living together. The purpose of this research is to look at the implementation of the Job Creation Act after it is legal as a law. This study uses a juridical-normative qualitative method with a statutory approach, a conceptual approach and a historical approach. The results of this study show that there are at least 7 sectors or clusters that get enough attention because the contents of the articles in them are said to be quite controversial. These clusters include the Investment and Business Activity Ecosystem Improvement cluster, the Employment Cluster Ease, Protection, and Empowerment of Cooperatives, Enterprises, Micro, Small and Medium Enterprises, the Ease of Doing Business cluster, the Research and Innovation Support cluster, the Land Acquisition cluster, and the Government Administration Implementation cluster.